Co‐composted biochar to decrease fertilization rates in cotton–maize rotation in Burkina Faso. (18th October 2021) - Cissé, Drissa; Cornelis, Jean‐Thomas; Traoré, Mamadou; Saba, Fatimata; Coulibaly, Kalifa; Lefebvre, David; Colinet, Gilles; Nacro, Hassan Bismack
Abstract: Agriculture in Burkina Faso relies on mineral fertilizers to reach decent crop production. Therefore, there is an urgent need to implement sustainable solutions that improve soil nutrient status while maintaining crop yields. Here we experiment with the recycling of nutrients through the production of biochar from cotton ( Gossypium hirsutum L.) stalks and its mixing with compost to improve soil properties of highly weathered Lixisol. The trials included three treatments: conventional compost (COMP‐100), co‐composted biochar (COMPBI‐100), each with recommended fertilization rates [cotton = 16.3 kg N ha –1, 15.1 kg P ha –1 and 17.4 kg of K ha –1 ; maize ( Zea mays L.) = 21.8 kg N ha –1, 20.1 kg P ha –1 and 23.2 kg K ha –1 ], and co‐composted biochar with 75% of recommended NPK fertilizer rate (COMPBI‐75). We amended the soil with compost at conventional rates used in Burkina Faso, that is, 2.5 t ha –1 at each crop year (2018 and 2019). We measured the effect of the amendments on cotton and maize yield cropped in rotation using a randomized block design with four replicates for each of the studied treatments. Our results showed that the soil properties and crop yield in COMPBI‐75 were not significantly lowered compared to COMPBI‐100, which did not differ compared to soil and plant responses in COMP‐100. Even not significant, COMPBI‐100 and COMPBI‐75 tend to have higher grain yields for cotton and maize. Our results highlight that co‐composted biochar may be a promising amendment to increase crop productivity parameters in Burkina Faso while decreasing the NPK doses. The reduction of fertilizer rates can have essential implications considering the socio‐economic and environmental advantages of reducing by quarter fertilizer doses in the Sudanese climatic region of Burkina Faso. Core Ideas: Soil was amended with conventional compost and co‐composted biochar. We investigated cotton and maize response during two cropping seasons in rotation. Soils are not influenced by biochar use in the compost neither by the decreasing NPK dose. Co‐composted biochar allows to achieve the same yields while using 75% of the recommended NPK.